2023
DOI: 10.1128/spectrum.00848-23
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis Infection and Associated Factors in Patients with Systemic Lupus Erythematosus: a Multicenter, Cross-Sectional Study

Abstract: The burden of tuberculosis and systemic lupus erythematosus in China ranks among the top three in the world. Therefore, active screening for LTBI and preventive intervention in SLE patients are of great significance in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…To further rule out the impact of glucocorticoids, treatment exposures were analysed in other patients with RMD, with or without indeterminate QFT. First, as a previous report suggested that prednisone equivalent ≥60 mg/day contributes to false-negative readout of the T-SPOT TB assay, 10 our samples were below this threshold. Second, no significant difference in glucocorticoid exposure was observed between the patients with RMD with or without indeterminate QFT.…”
Section: Resultsmentioning
confidence: 61%
“…To further rule out the impact of glucocorticoids, treatment exposures were analysed in other patients with RMD, with or without indeterminate QFT. First, as a previous report suggested that prednisone equivalent ≥60 mg/day contributes to false-negative readout of the T-SPOT TB assay, 10 our samples were below this threshold. Second, no significant difference in glucocorticoid exposure was observed between the patients with RMD with or without indeterminate QFT.…”
Section: Resultsmentioning
confidence: 61%